DESIGN OF THE GREATEST COMMON DIVISOR (GCD) USING THE SHARING CONTEXT - Mistawan, Kadek; Somakim, Somakim; Hapizah, Hapizah
This study aims to determine the role of sharing context in supporting the learning of the greatest common divisor (GCD) in class IV. The learning approach used is the Indonesian realistic mathematical approach (PMRI) which uses context. The use of context aims as a starting point in mathematics learning. The context used is sharing, in which students share candy and eggs with their classmates. It is hoped that using context relating to daily life can make learning more meaningful and students can build their own mathematical knowledge. The method used in this research is Design Research type Validation Study which includes preliminary design, teaching experiment, and retrospective analysis. The subjects consisted of 30 students of the IVD class and a mathematics teacher at SD Negeri 157 Palembang. Data collection techniques were obtained from video recordings, student activity sheets and interviews which were then analyzed qualitatively. A series of activities demonstrated that the context of sharing can help students understand the concept of the greatest common divisor (GCD) so as to guide students in solving problems related to the greatest common divisor (GCD).